Toward “English” Phonetics: Variability in the Pre-consonantal Voicing Effect Across English Dialects and Speakers - Tanner, James; Sonderegger, Morgan; Stuart-Smith, Jane; Fruehwald, Josef (Frontiers in Artificial Intelligence, 2020)
Recent advances in access to spoken-language corpora and development of speech processing tools have made possible the performance of `large-scale' phonetic and sociolinguistic research. This study illustrates the usefulness of such a large-scale approach – using data from multiple corpora across a range of English dialects, collected and analysed with the SPADE project – to examine how the pre-consonantal Voicing Effect (longer vowels before voiced than voiceless obstruents, in e.g. bead vs beat) is realised in spontaneous speech, and varies across dialects and individual speakers. Compared with previous reports of controlled laboratory speech, the Voicing Effect was found to be substantially smaller in spontaneous speech, but still influenced by the expected range of phonetic factors. Dialects of English differed substantially from each other in the size of the Voicing Effect, whilst individual speakers varied little relative to their particular dialect. This study demonstrates the value of large-scale phonetic research as a means of developing our understanding of the structure of speech variability, and illustrates how large-scale studies, such as those carried out within SPADE, can be applied to other questions in phonetic and sociolinguistic research.